Diagnosis of Tubercular Lymphadenitis by PCR of Fine Needle Aspirates - Parvez, Masud; Mohiuddin, Md; Hassan, Md Zahid; Ahmad, Farooque; Haq, J Ashraful (Ibrahim Medical College Journal, 2013)
A definitive and accurate diagnosis of tubercular lymphadenitis is important for its proper management. Fine needle aspiration cytology (FNAC) is an easy procedure for collection of material for cytopathological and bacteriological examination. But the detection rate of M. tuberculosis from the aspirated material is low with Ziehl-Neelson (Z-N) stain and even with culture. Polymerase chain reaction (PCR) is a rapid method for diagnosis of tuberculosis from various clinical samples. In the present study, PCR was employed for the detection of mycobacterial DNA sequences in fine needle aspirates of twenty cases of suspected tubercular lymphadenitis and compared with cytomorphological characteristics, Z-N stain and culture. Thermo stable multiplex PCR was used to detect Mycobacterium specific DNA. The rate of PCR positivity for mycobacterial DNA was 70% as compared to 50% and 60% by Z-N stain and culture respectively. Papanicolaou as well as Hematoxylin and Eosin (H&E) stains of fine needle aspirated (FNA) materials detected granulomatous lesions suggestive of tubercular infection in only 50% cases. FNAC with Type 3 cytomorphological pattern without presence of granuloma yielded highest positivity rate by PCR. PCR was found more sensitive technique to detect Mycobacterium in patient with tubercular lymphadenitis. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14728 Ibrahim Med. Coll. J. 2012; 6(2): 46-49